1997
DOI: 10.1007/bf02767025
|View full text |Cite
|
Sign up to set email alerts
|

PCR-based genotyping of MNSs blood group: Subtyping of M allele to MG and MT

Abstract: SummaryPCR-based genotyping of MNSs blood group system was investigated in combination with restriction fragment length polymorphism (RFLP), single-strand conformation polymorphism (SSCP) and allele-specific PCR amplification (ASPA) techniques. M and N alleles are based on three nucleotide substitutions in exon 2 and one base change (G or T) in an intron of glycophorin A locus. The latter single base change was also found among M alleles analyzed in this study, so that M allele appeared to be subdivided into M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In our previous studies, M and N alleles were classified into six variations, provisionally called MN*M101, M102, M201, M202, N101 and N102, from the sequencing results of a total of 12,576 bp from the 5¢-flanking region to exon 7 of the GPA gene, with the exception of 30 kb of intron 1 (Akane et al 1997(Akane et al , 2000Mizukami et al 2002). These studies also revealed sequence data for new alleles M103, N103, N104 (N V ) and N201 (N 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous studies, M and N alleles were classified into six variations, provisionally called MN*M101, M102, M201, M202, N101 and N102, from the sequencing results of a total of 12,576 bp from the 5¢-flanking region to exon 7 of the GPA gene, with the exception of 30 kb of intron 1 (Akane et al 1997(Akane et al , 2000Mizukami et al 2002). These studies also revealed sequence data for new alleles M103, N103, N104 (N V ) and N201 (N 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…MN serological phenotyping and genotyping were performed as reported previously (Nakayashiki and Sasaki 1996;Akane et al 1997;Li et al 1998;Sasaki et al 2000). Two new N alleles had been named temporarily N 2 and N v (Sasaki et al 2000) and are named N201 and N104, respectively, in this paper.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycophorin A (GPA), a sialoglycoprotein on the erythrocyte membrane, carries M and N antigens, based on two changes of the amino acid sequence at positions 1 and 5 (M, serine and glycine; N, leucine and glutamic acid). M and N alleles of the GPAgene are attributed to three nucleotide substitutions in exon 2 ( Figure 1) (10,18) and are determined by restriction fragment-length polymorphism (RFLP) analysis (1,6,12), single-strand conformation polymorphism (SSCP) analysis of the polymerase chain reaction (PCR) products (1) or allele-specific PCR amplification (ASPA) (4,8,13). MN genotyping by DNA analysis is informative for forensic identification and in several clinical situations where serological phenotyping is difficult or impossible (8), such as (i) in a patient transfused with large amounts of blood from various donors, (ii) a fetus at risk for hemolytic disease and (iii) a patient with autoimmune hemolytic anemia.…”
mentioning
confidence: 99%